Impact of school type on the posture and psychological state of Egyptian adolescent girls: An observational study. Issue 1 (31st December 2022) - Saeed, Doaa; Ahmed, Hamada; Metwally, Fahima; Yousef, Amel M.; Koura, Ghada; Khaled, Osama Ahmed; Yosri, Mahitab M
Abstract: The school type can greatly affect the posture and psychological state of adolescent girls by controlling many factors, such as school bag load and way of carriage, furniture-anthropometry degree of matching, and availability of resources. This study aimed to compare postural changes and psychological aspects of adolescent Egyptian girls, attending two different school types: public versus private schools. An observational study was conducted on 200 adolescent girls, whose ages ranged from 14 to 17 years, with a body mass index of 19–25 kg/m 2, selected from two different school types (two public and another two private) at El-Sharkia government, Egypt. They were assigned into two equal groups: group (A), including 100 public schoolgirls, and group (B) involving 100 international schoolgirls. Postural and mechanical changes were assessed at the head, rib cage, shoulders, hips, and knees in both groups by the Posture Screen® Mobile app and a photographic method from lateral and frontal views while standing. Assessing anxiety, depression, and stress signals was done using depression anxiety stress scales-21. The girls of public and international schools had different schoolbag characteristics but assumed the same poor posture. The results indicated more significant changes in the public schoolgirls of group (A) ( p ˂ 0.05) in the head shift, shoulder tilting, hip shift, hip tilting, total shift, and total tilting, compared to the international girls of the group (B), while there were more changes in head weight, and effective head weight, indicating more forward head in the international girls of the group (B). For psychological aspects, the public-school girls had statistically significantly higher stress and anxiety scores (p ˂ 0.05) than the international schoolgirls. Thus, it could be concluded that the school type may affect the posture and psychology of Egyptian adolescent girls, as the girls at the public schools had more coronal postural changes together with more stress and anxiety than the girls enrolled in the private schools, while girls of the private schools had more forward head posture.